Selective admissions in higher education : public policy and academic policy : the pursuit of fairness in admissions to higher education : the status. (San Francisco, California : Jossey-Bass Inc., Publishers, 1977)
Admissions policy for selective schools has long been a concern within higher education. Recently, it has become an issue for public policy as well at the legislative, the administrative, and the judicial levels. Policy and procedures in this area are now (fall 1977) before the Supreme Court of the United States in the case of The Regents of the University of California v. Allan Bakke. The Carnegie Council and the Carnegie Commission on Higher Education before it had been continuously interested in this issue and related matters.' It is out of this background of concern by the Commission and the Council that the Carnegie Council approaches the current issue.
1. The Points at Issue -- 2. The Central Role of Values in Pursuing Fairness in Admissions -- 3. Institutions and Individuals in the Admissions Process -- 4. Arguments for Consideration of Race in Admissions Policies -- 5. Educational Due Process in Admissions -- 6. A Two-Stage Model of the Admissions Process -- 7. Special Programs -- 8. Decision Strategies -- 9. Summary and Conclusions.
Includes bibliographical references and index.
Keywords: COLLEGE ADMISSION